The elimination of metaphysics through logical analysis of language - Carnap Рудольф (Actual Problems of Mind, 2023)
Translation of Rudolf Carnap’s program article "The elimination of metaphysics through logical analysis of language", made according to the edition Carnap R. Uberwindung der Metaphysik durch ¨ logische Analyse der Sprache. Erkenntnis. 2. Bd. 1931. S. 219-241.